Root canal treatment of a mandibular second premolar with three roots and canals - an anatomic variation. - Bhavana Gandhi; Anand C Patil (Tehran University of Medical Sciences, 2013)
Dental anatomical variations play a significant role in the diagnosis and a successful treatment outcome in endodontics. It is essential for the clinician to have a clear picture and understanding of the pulpal anatomy and its variations. In a mandibular second premolar, it is rare to find extra roots and canals. The aim of the present article is to report a case about the successful diagnosis, and clinical management of a three-rooted mandibular second premolar with three independent roots and canals.